Learning how programs achieve their impact: Embedding theory-driven process evaluation and other program learning mechanisms in Alive & Thrive - Rawat, Rahul; Nguyen, Phuong Hong; Ali, Disha; Saha, Kuntal K.; Alayon, Silvia; Kim, Sunny S.; Ruel, Marie T.; Menon, Purnima (SAGE Publications, 2013)
Traditionally, impact evaluations have focused primarily on answering what impact programs or interventions have, with less attention to how or why impacts are achieved, or not achieved. The Alive & Thrive initiative, a 6-year program that aims to improve infant and young child feeding (IYCF) practices and reduce stunting in Bangladesh, Ethiopia, and Vietnam, has a specific objective to generate learning on how to achieve and replicate Alive & Thrive's impact.In Alive & Thrive, theory-driven process evaluation methods are the primary mechanism through which data are generated to address this objective. This paper focuses on the different methodological approaches that are being utilized, to answer the critical “how”; questions, and to generate information on the many processes and pathways to program impact.We identify four key principles in our methodological approach that guides all process evaluation activities: 1) developing detailed program impact pathway (PIP) models, 2) linking data collection to PIPs utilizing mixed methods and multiple data sources, 3) linking evaluation activities with program implementation timelines, and 4) engaging with the program implementation and management teams.Beginning with the launch of the program, we outline the steps that have been taken in the design and implementation of the process evaluations of Alive & Thrive, and provide examples of how these steps have been operationalized in different country contexts.This theory-driven and country- and component-specific approach, centered on careful analysis of PIPs, is intended to generate information on implementation and utilization pathways of Alive & Thrive's interventions, thereby answering the questions of how impacts are achieved, or why not. This evaluation approach is not without challenges, and we highlight some of these key challenges.